PHYTOCHEMICAL AND ORGANOLEPTIC CHARACTERISTIC OF Sterculia quadrifida R.Br. TREE BARK HERBAL TEA - Siswadi; Heny Rianawati; Grace Serepina Saragih; Retno Setyowati (APTKLHI, 2023)
Sterculia quadrifida R.Br. Bark decoction is used to treat hepatitis and consumed as a tonic by Timorese in the East Nusa Tenggara Province, Indonesia. Raw herbal materials are susceptible to fungi contamination, have limitations in transportation, and have low economic value. Processing the bark into powder packed in tea bags is expected to overcome these obstacles. Stevia, ginger, and mint leaves are herbs often added to herbal drink formulas. This study aimed to evaluate the antioxidant capacity, total flavonoid content (TFC), total phenol content (TPC), physicochemical properties, and sensory properties of six formulas, namely: (F1) pure S. quadrifida bark; (F2) bark of S. quadrifida and leaves of stevia; (F3) stem bark of S. quadrifida and ginger; (F4) bark of S. quadrifida, stevia, and ginger; (F5) bark of S. quadrifida and mint leaves; (F6) bark of S. quadrifida, stevia, and mint. Total phenolic content was measured using the Folin-Ciocalteu method, and total flavonoids were determined using the AICI3 method. Antioxidant activity was measured using the 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) method. The TPC of S. quadrifida tea ranged from 14.09±0.7 to 68.20±0.95% Gallic Acid Equivalent (GAE), and the TFC ranged from 0.03±0.005 to 0.09±0.004% QE. The Ascorbic acid Equivalent Antioxidant Capacity (AEAC) of F1, F2, F5, and F6 were insignificantly different. F1 contained the highest levels of antioxidants (1,044.3±28.48 ppm Ascorbic Acid Equivalent (AAE)). Formulas with the addition of stevia, mint, and ginger showed weaker antioxidant activity than pure S. quadrifida. F1 and F2 have the potential to be developed as commercial herbal teas